Intrusion and contamination of high-temperature dunitic magma: The Nordre Bumandsfjord pluton, Seiland, Arctic Norway - Griffin, W.; Sturt, B.; O'Neill, C.; Kirkland, Chris; O'Reilly, S. (2013)
The Caledonian Nappe Complex of Arctic Norway provides rare insights into the interaction between mafic-ultramafic magmas and the deep continental crust. The Kalak Nappe Complex contains >25,000 km3 of mafic igneous rocks, mostly layered gabbros, making up the 570-560 Ma Seiland Igneous Complex. The complex has been intruded by a series of ultramafic magmatic rocks, including the Nordre Bumandsfjord pluton. Field relationships in this pluton show that extremely fluid, dry, relatively Fe-rich (Fo81) dunite magmas intruded a pile of cumulate gabbros, with block stopping and intrusive brecciation. Diking on scales from mm to metres and extensive melting and assimilation of the gabbros attest to high temperatures, consistent with a 2-km-wide granulite-facies contact aureole. Major- and trace-element trends show that the dunites were progressively contaminated by a cpx-rich partial melt of the gabbros, producing a range of lithologies from dunite through lherzolites to wehrlite. Experimental studies of natural samples at 0. 8-1 GPa define the dunite solidus at 1,650-1,700 °C. In the average peridotite, contamination has produced a crystallisation interval of ca 400 °C (1,600-1,200 °C); this would provide large amounts of heat for melting and metamorphism and would maintain the fluidity of the magmas to relatively low T, consistent with field relationships.Thermochemical and dynamic modelling demonstrates that the dunitic primary magmas may represent the last melting of a rapidly ascending diapir of previously depleted subducted oceanic lithosphere. The mafic rocks of the Seiland Complex may already have been extracted from this diapir, and the late dikes of the province may reflect melting of the asthenosphere as the diapir spread out beneath the lithosphere. Ultramafic magmas, abundant in the Archean, may still be more common than usually assumed. However, they would only penetrate to the shallow crust under unusually extensional conditions, where ascent could outpace assimilation.